2010
DOI: 10.1021/nl9039718
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent Structural DNA Nanoballs Functionalized with Phosphate-Linked Nucleotide Triphosphates

Abstract: Highly labeled DNA nanoballs functionalized with phosphate-linked nucleotide triphosphates (dNTPs) were developed as a source of dNTPs for DNA polymerase. The particles were prepared by strand-displacement polymerization from a self-complementary circular template. Imaged by atomic force microscopy, these functionalized particles appear as condensed fuzzy balls with diameters between 50-150 nm. They emit a bright fluorescent signal, detected in 2 msec exposures with a signal-to-noise of 25 when imaged using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Inspired by nature, we present herein the noncanonical self-assembly of hierarchical DNA nanoflowers (NFs) with densely packed DNA and built-in multifunctional moieties for biomedical applications. Using only a low amount of two DNA strands (one template and one primer), long building blocks were generated via rolling cycle replication (RCR), an isothermal enzymatic reaction involving the replication of many circular genomic DNAs (e.g., plasmids or viral genomes), the regulation of some eukaryotic tandem genes, , and applications in biotechnology. ,,, Without reliance on Watson–Crick base-paring, NFs were self-assembled through liquid crystallization of the resultant long building blocks, instead of conventionally used short DNA. The sparsity of nick sites in the elongated building blocks and the compactness of DNA in NFs are expected to increase the resistance of NFs to nuclease degradation, denaturation, or dissociation at low concentrations, and the exceptional biostability was demonstrated by the maintenance of NF structural integrity under the treatment with nucleases, human serum, high temperature, urea, or dilution, making NFs amenable for versatile biomedical situations.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by nature, we present herein the noncanonical self-assembly of hierarchical DNA nanoflowers (NFs) with densely packed DNA and built-in multifunctional moieties for biomedical applications. Using only a low amount of two DNA strands (one template and one primer), long building blocks were generated via rolling cycle replication (RCR), an isothermal enzymatic reaction involving the replication of many circular genomic DNAs (e.g., plasmids or viral genomes), the regulation of some eukaryotic tandem genes, , and applications in biotechnology. ,,, Without reliance on Watson–Crick base-paring, NFs were self-assembled through liquid crystallization of the resultant long building blocks, instead of conventionally used short DNA. The sparsity of nick sites in the elongated building blocks and the compactness of DNA in NFs are expected to increase the resistance of NFs to nuclease degradation, denaturation, or dissociation at low concentrations, and the exceptional biostability was demonstrated by the maintenance of NF structural integrity under the treatment with nucleases, human serum, high temperature, urea, or dilution, making NFs amenable for versatile biomedical situations.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleotide adenosine (A) was strategically spaced along the DNA template, providing regular positions to attach the multidye-modified dUTPs on the replicated product. It has been reported that dye-modified dUTPs can be recognized by many DNA polymerases, including F29, [16] enabling their incorporation into NFs. Accordingly, FAM, Cy3 and ROX were chosen to build the FRET cascades required to implement our multifluorescent imaging platform.…”
mentioning
confidence: 99%
“…The circularized templates are amplified by a Phi 29 polymerase and are called a DNA nanoball (DNB) [33]. Up to three billion DNBs are then selectively attached to a silicon chip.…”
Section: Nanopore Sequencingmentioning
confidence: 99%